CONCENTRATION AND FLUXES OF DISSOLVED ORGANIC CARBON (DOC) IN THREE NORWAY SPRUCE STANDS ALONG A CLIMATIC GRADIENT IN SWEDEN - Fröberg M.; Berggren D.; Bergkvist B.; Bryant Ch.; Mulder Ja. (My University, 2006)
Leaching of dissolved organic carbon (DOC) from the forest floor and transport in soil solution into the mineral soil are important for carbon cycling in boreal forest ecosystems. We examined DOC concentrations in bulk deposition, throughfall and in soil solutions collected under the O and B horizons in three Norway spruce stands along a climatic gradient in Sweden. Mean annual temperature for the three sites was 5.5, 3.4 and 1.2 °C. At each site we also examined the effect of soil moisture on DOC dynamics along a moisture gradient (dry, mesic and moist plots). To obtain information about the fate of DOC leached from the O horizon into the mineral soil, 14C measurements were made on bulk organic matter and DOC. The concentration and fluxes of DOC in O horizon leachates were highest at the southern site and lowest at the northern. Average DOC concentrations at the southern, central and northern sites were 49, 39 and 30 mg l−1, respectively. We suggest that DOC leaching rates from O horizons were related to the net primary production of the ecosystem. Soil temperature probably governed the within-year variation in DOC concentration in O horizon leachates, but the peak in DOC was delayed relative to that of temperature, probably due to sorption processes. Neither soil moisture regime (dry, mesic or moist plots) nor seasonal variation in soil moisture seemed to be of any significance for the concentration of DOC leached from the O horizon. The 14C measurements showed that DOC in soil solution collected below the B horizon was derived mainly from the B horizon itself, rather than from the O horizon, indicating a substantial exchange (sorption–desorption reactions) between incoming DOC and soil organic carbon in the mineral soil.
Keywords: CLIMATIC GRADIENT; DISSOLVED ORGANIC CARBON; FOREST SOIL; RADIOCARBON